The ANALYSIS OF AN AUXILIARY FUZZY LOGIC BASED STATIC SYNCHRONOUS SERIES COMPENSATOR (International Journal of Engineering Management Science, 2022)
Low Frequency Oscillations (LFO) occur in power systems because of lack of the damping torque. Low frequency oscillations (LFO) are a frequent adverse phenomenon which increase the risk of instability for the power system and thus reduce the total and available transfer capability (TT C and ATC). This brief investigates the damping performance of the static synchronous series compensator (SSSC) equipped with an auxiliary fuzzy logic controller (FLC). This manuscript investigates the damping performance of the Static Var Compensator (SVC) equipped with an auxiliary controller based on Adaptive Neuro-Fuzzy Inference System (ANFIS). First of all, a modified Heffron-Phillips model of the single machine infinite bus (SMIB) system installed with SVC is established. In the following an auxiliary fuzzy logic controller (FLC) for SVC is designed to enhance the transient stability of the power system. Next, an ANFIS based auxiliary damping controller is well designed and compared with the FLC. In order to evaluate the performance of the proposed ANFIS based controller in damping of LFO, the SMIB power system is subjected to a disturbance such as changes in mechanical power. The complete digital simulations are performed in the MATLAB/Simulink environment to provide comprehensive understanding of the issue. Simulation results demonstrate that the developed ANFIS based controller would be more effective in damping electromechanical oscillations in comparison with the FLC and conventional proportional integral (PI) controller.